PENGARUH PENERAPAN MODUL AJAR ARITMATIKA SOSIAL PADA KEMAMPUAN PEMECAHAN MASALAH DAN PEMAHAMAN LITERASI FINANSIAL - Fredy Fredy; Mohamad Ilham; Rizki Adri Yohanes; Hafsemi Rapsanjani; Wa Ode Siti Hamsinah Day (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
The tendency in math learning in classrooms is for teachers to explain the material according to what is in the available textbooks without making efforts to develop learning in accordance with the contextual realities of students' daily lives. As a result, students face difficulties in solving mathematical problems when encountering issues different from the example problems provided by the instructor. This research aims to implement a problem-based social arithmetic teaching module based on the contextual approach of Papua. The subsequent application's results will be observed to determine if it has an impact on students' problem-solving abilities and financial literacy comprehension in elementary schools. The research stages include preparation, implementation, and evaluation. Data collection for this research is done through observation, interviews, and tests of students' problem-solving abilities and financial literacy comprehension. The research findings indicate that there is a partial difference in problem-solving abilities and financial literacy comprehension between students taught with the arithmetic teaching module and those taught with the conventional teaching module used in schools. It can be concluded that there is a partial influence on students' problem-solving abilities and financial literacy comprehension taught using the arithmetic teaching module and those taught using the conventional teaching module used in schools.